Advanced technologies management for retailing frameworks and cases - Pantano, Eleonora; Timmermans, Harry J. P. (Premier reference source, 2011)
"This book contributes to our understanding of applications of new technologies and their impact on the design and development of point of sale systems and on consumers' behavior" - Provided by publisher